Effective learning among Malaysian juveniles: Key elements for success - Noor Insyiraah binti Abu Bakar, Mohd Muslim Md Zalli, Izazol Idris, Azlina Abu Bakar, Abdul Talib Mohamed Hashim, Nor Hasnida Che Md Ghazali, Mohd Nazir Md Zabit (Tanjung Malim, 2024)
Effective learning among Malaysian juveniles: Key elements for success by Noor Insyiraah binti Abu Bakar, Mohd Muslim Md Zalli, Izazol Idris, Azlina Abu Bakar, Abdul Talib Mohamed Hashim, Nor Hasnida Che Md Ghazali, Mohd Nazir Md Zabit